ASURANSI MIKRO UNTUK MODA TRANSPORTASI OJEK OJEK - Rukaesih A. Maolani; Acmad Sudiyar Dalimunthe (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
This study aimed  at finding out “Ojek’s”  drivers’ knowledge about micro insurance and their interest in becoming  the customers. The study  used 60 “Ojek’s”  drivers as respondents. It was conducted in several areas of Jakarta and Bekasi from October 2017 to January 2018.. The data were collected through questionnaires and analyzed using descriptive statistics.  The conclusion obtained is most of “Ojek’s”  drivers in the study sites already knew about  micro insurance but only few of them who are interested in becoming the insurance customers.